A survey on the floral diversity of rural areas in Udumalpet Taluk, Tiruppur District, Tamil Nadu, India (Bangladesh Journal of Plant Taxonomy, 2020)
Survey on the floral diversity is an important activity to assess the existing flora. This study was carried out from December 2017 to December 2018 to document the flora existing in the Udumalpet Taluk, Tiruppur District, Tamil Nadu, India. As a result, a total of 370 taxa belonging to 263 genera of 82 angiosperm families have been documented. 52% of species of them are herbaceous. Euphorbiaceae and Fabaceae with 23 taxa each, Asteraceae with 21 species, Acanthaceae with 20 species and Amaranthaceae with 18 species are observed as the dominant families. In this article, family, botanical name, habit, vernacular name and various applications of the recorded plants are enumerated systematically. Threats to these plants and possible conservation strategies are also discussed briefly.Bangladesh J. Plant Taxon. 27(1): 137-152, 2020 (June)